Stock Market Integration and the Impact of the Subprime Financial Crisis: A Malaysian Perspective - Lee, Siew-Peng; Isa, Mansor (Asian Journal of Business and Accounting, 2014)
Using weekly data over the period 2002-2011, we examine market integration among 22 international markets from the viewpoint of Malaysian investors. We also analyse the impact of the subprime financial crisis of 2007-2008 on the linkages of these markets. In general, our results indicate a lack of cointegration in all market groups. We find that the subprime crisis has resulted in a temporary cointegration in the groups during the peak of the crisis, but cointegration is weak or absent in the pre- and post-crisis periods. We also find that cointegration is strongest in the Malaysian and European market groups and surprisingly weak in the group involving Malaysia and its neighbouring emerging markets. The results of the causality and variance decomposition analyses strongly indicate that Malaysia is largely unrelated with other markets. Overall, our evidence points towards the possibility for diversification benefits to local investors. Keywords: Stock Market Integration, Subprime Crisis, Cointegration, Structural Breaks, Granger Causality, Variance Decomposition JEL: F30, F36, G15